Implementasi Media Pembelajaran Berbasis Ecoprint Untuk Meningkatkan Perkembangan Motorik Siswa di TK Bunga Bangsa - Mughnifatus Sa’ada, Siti; Miftahul Munif, Moh. Vito (Fakultas Agama Islam, 2024)
Ecoprint is managing fabrics in a natural way. All the materials used are natural, such as flowers, leaves, even tree branches. As the name suggests, ecoprint comes from the English words eco (ecosystem) which means nature and print which means printing. This batik is made by printing with the bahak that is around. Ecoprint is called unique because it cannot be repeated. The dyes used are not the same; that the dyes used in one place and another are different. The results of this research show that the ecoprint technique planning at Kindergarten Al Hidayah III makes it a habit to train fine motor skills, apart from that the ecoprint technique also introduces various media that tend to use natural materials. In planning the ecoprint technique, there is still a lot that needs to be prepared to ensure smooth learning, such as the media or materials that will be used, for example pounding tools or stones, various types of leaves that contain high levels of natural dyes. The results of this research show that planning the ecoprint technique in Al Kindergarten Hidayah III makes it a habit to train his fine motor skills, apart from that, ecoprint technique also introduces various media that tend to use natural materials. In planning the ecoprint technique, there is still a lot that needs to be prepared to ensure smooth learning, such as the media or materials that will be used, for example crushing tools or stones, various types of leaves that contain high levels of natural dyes.